Differential expression of olfactory genes in Atlantic salmon (Salmo salar) during the parr–smolt transformation. Issue 24 (28th November 2019) - Madsen, Steffen S.; Winther, Sara S. T.; Bollinger, Rebecca J.; Steiner, Ulrich; Larsen, Martin H.
Abstract: The anadromous salmon life cycle includes two migratory events, downstream smolt migration and adult homing migration, during which they must navigate with high precision. During homing migration, olfactory cues are used for navigation in coastal and freshwater areas, and studies have suggested that the parr– smolt transformation has a sensitive period for imprinting. Accordingly, we hypothesized that there would be significant changes in gene expression in the olfactory epithelium specifically related to smoltification and sampled olfactory rosettes from hatchery‐reared upper growth modal juvenile Atlantic salmon at 3‐week intervals from January to June, using lower growth modal nonsmolting siblings as controls. A suite of olfactory receptors and receptor‐specific proteins involved in functional aspects of olfaction and peripheral odor memorization was analyzed by qPCR. Gene expression in juveniles was compared with mature adult salmon of the same genetic strain caught in the river Gudenaa. All mRNAs displayed significant variation over time in both modal groups. Furthermore, five receptor genes ( olfc13.1, olfc15.1, sorb, ora2, and asor1 ) and four olfactory‐specific genes ( soig, ependymin, gst, and omp2 ) were differentially regulated between modal groups, suggesting altered olfactory function during smoltification. Several genes were differentially regulated in mature salmon compared with juveniles, suggesting that homing and odor recollection involve a different set of genes than during imprinting. Thyroid hormone receptors thrα and thrβ mRNAs were elevated during smolting, suggesting increased sensitivity to thyroid hormones. Treatment of presmolts with triiodothyronine in vivo and ex vivo had, however, only subtle effects on the investigated olfactory targets, questioning the hypothesis that thyroid hormones directly regulate gene expression in the olfactory epithelium. Abstract : Imprinting in salmon involves odor recognition. This study analyzed 17 olfactory‐related genes in Atlantic salmon on a detailed time course during the parr–smolt transformation. The results identified five receptor genes and four olfactory‐specific genes that were differentially regulated, supporting olfactory differentiation prior to downstream migration, which may be involved in imprinting and subsequent homing.